The Influence of Self-Care and Self-Compassion Behavior on Students' Mental Well-Being Through Resilience Mediator: An Islamic Psychological Perspective - Suud, Fitriah M.; Rachmawati Musslifah, Anniez; Purnomosidi, Faqih (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
University students today face increasing academic demands, social pressures, and rapid sociocultural changes that may affect their mental well-being. From an Islamic psychological perspective, inner strength and balance are essential for maintaining psychological health. This study aims to examine the relationships between self-care behavior, self-compassion, resilience, and students’ mental well-being, with a particular focus on the mediating role of resilience. A cross-sectional survey was conducted with 361 university students using a non-probability sampling technique, and the data were analyzed using Structural Equation Modeling, Partial Least Squares (SEM-PLS). The findings indicate that resilience is strongly associated with students’ mental well-being, highlighting its central role as a key psychological resource. Self-care behavior is positively related to both resilience and mental well-being, with resilience acting as an important pathway linking self-care to improved well-being. However, self-compassion does not demonstrate a significant positive relationship with resilience or mental well-being, suggesting that its role may vary across cultural contexts, particularly in non-Western settings. These findings underscore the importance of promoting resilience and adaptive self-care as central components of student mental health interventions. From an Islamic psychological perspective, resilience reflects inner endurance, patience (sabr), and spiritual balance, offering a culturally grounded framework for understanding well-being. This study contributes to a more context-sensitive and integrative approach to student mental health by highlighting the dynamic interaction between behavioral and psychological resources.